2007
DOI: 10.2139/ssrn.567650
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure Decisions: Which Factors are Reliably Important?

Abstract: This paper examines the relative importance of many factors in the capital structure decisions of publicly traded American firms from 1950 to 2003. The most reliable factors for explaining market leverage are: median industry leverage (+ effect on leverage), market‐to‐book assets ratio (−), tangibility (+), profits (−), log of assets (+), and expected inflation (+). In addition, we find that dividend‐paying firms tend to have lower leverage. When considering book leverage, somewhat similar effects are found. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

119
831
16
40

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 551 publications
(1,006 citation statements)
references
References 84 publications
119
831
16
40
Order By: Relevance
“…Following Graham and Tucker (2006) and Frank and Goyal (2009), I use control variables known to affect the capital structure. Several studies have shown that depreciation and investment tax credits, as NDTS, substitute for debt (MacKie-Mason 1990;Dhaliwal et al 1992;Trezevant 1992).…”
Section: Control Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Graham and Tucker (2006) and Frank and Goyal (2009), I use control variables known to affect the capital structure. Several studies have shown that depreciation and investment tax credits, as NDTS, substitute for debt (MacKie-Mason 1990;Dhaliwal et al 1992;Trezevant 1992).…”
Section: Control Variablesmentioning
confidence: 99%
“…I include ROA as a control for the effect of profitability on the use of debt. In addition, since Frank and Goyal (2009) document that firms with highly collateralizable assets, such as inventory, property, plant, and equipment, use more debt, I include a collateral variable, the proportion of assets that are collateralizable, as a control variable. All of the independent variables, with the exception of Dep, IndDebt/asset and Lag5(debt/asset), are lagged by one period, because their current year values could have been affected by debt policy.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of this theory of equity market timing are that there should be an inverse relationship between capital structure and market value, and that the adjustment of the capital structure to its target level is a long and slow process. However, considerable theoretical development and empirical testing are needed (Frank and Goyal, 2004) before this can stand as an independent theory.…”
Section: Equity Market Timing and Capital Structurementioning
confidence: 99%
“…The contribution of this paper can be outlined in two elements: (a) it is the first attempt to employ subset selection criteria for capital structure modeling in a transition market, (b) In this study, the authors employ ten subsets selection criteria, while recently, using data from a developed market, Frank and Goyal (2004) present a study of choosing the most reliable determinants of capital structure. They used only one criterion, which is the Bayesian Information Criterion (BIC), for the purpose of subset selection.…”
mentioning
confidence: 99%